CrAlTiSiN coating and preparation method thereof
By doping Ti and Si elements into the CrAlN coating, the CrAlTiSiN coating was prepared, which solved the problems of low hardness and insufficient corrosion resistance of the CrN coating, and achieved higher hardness, elastic modulus and corrosion resistance, significantly improved the overall performance of the coating.
Patent Information
- Application Number
- CN202510052584.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-14
AI Technical Summary
Due to its low hardness, large friction resistance and relatively weak corrosion resistance, CrN coatings limit its application range, and the existing CrAlN coatings still have room for improvement in overall performance.
By doping Ti and Si elements, a CrAlTiSiN coating was prepared, and it was deposited under specific conditions using multi-arc ion plating technology to form a coating with high hardness and good tissue structure.
The hardness, elastic modulus and fracture toughness of CrAlTiSiN coating are improved, its corrosion resistance and cutting performance are enhanced, and its application range is expanded.
Smart Images

Figure CN119776779A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of coatings, and in particular to a CrAlTiSiN coating and a preparation method thereof. Background Art
[0002] CrN coating is widely used in automotive molds, cutting tools and easily worn parts because of its superior friction and wear resistance and corrosion resistance compared with TiSiN coating. However, due to factors such as low hardness, high friction resistance and relatively weak corrosion resistance, the application of CrN is limited to a certain extent. At present, the comprehensive performance of CrAlN ternary coating has been improved to a certain extent compared with CrN coating.
[0003] In recent years, researchers have added non-metallic elements such as Si and B into CrAlN coatings and found that the doped coatings present typical nanocrystalline and amorphous structures. 3 N 4 ) is a ceramic phase with high hardness and high brittleness, but at the same time the three-dimensional network structure of Si 3 N 4 Unlike general ceramic materials, it has low thermal expansion coefficient, high elastic modulus and high strength. x ) is the most stable structure.
[0004] CrAlSiN coatings with different Si contents were studied. The microstructure of the coatings consists of (Cr, Al)N microcrystals and amorphous Si 3 N 4 Phase composition: With the increase of Si content, the corrosion resistance of CrAlSiN coating gradually improves. The main reason is that the passivation layer formed on the coating surface will hinder the corrosion medium from penetrating into the substrate, thereby improving the corrosion resistance of CrAlSiN coating.
[0005] Some researchers have also prepared CrAlTiN and CrAlTiSiN coatings by multi-arc ion plating technology. Comparative analysis shows that the maximum hardness of CrAlTiN is 29GPa. The increase in the hardness of CrAlTiSiN coating is related to the Si content. Its maximum hardness is 37GPa, the friction coefficient is 0.58, and the film-base bonding force exceeds 50N. The cutting performance of CrAlTiSiN coating is significantly improved compared with CrAlTiN. The main reason for the increase in the hardness of CrAlTiSiN coating is that the Si element is in the form of amorphous Si 3 N 4 The structural encapsulation of nanocrystalline CrAlN causes solid solution strengthening and Si element doping causes grain refinement, thereby improving the hardness of the coating.
[0006] Therefore, the doping of elements has a significant effect on the properties of CrAlN coatings. Summary of the invention
[0007] Based on this, the purpose of the present disclosure is to further improve the properties of the CrAlN coating by doping so as to make its application more extensive.
[0008] To achieve the above objectives, the present disclosure provides the following technical solutions:
[0009] A method for preparing a CrAlTiSiN coating comprises the following steps:
[0010] S1. Pass N into the coating chamber 2 , start the Cr target and deposit a CrN transition layer on the substrate;
[0011] S2. Continue to enter N 2 , turn off the Cr target, start the CrAl target and TiSi target, and 2 Depositing CrAl and TiSi on the substrate at a flow rate of 100 to 300 sccm to obtain a CrAlTiSiN coating;
[0012] The bias voltage of the CrAl target is -100 to -90 V, and the current is 110 to 130 A; the bias voltage of the TiSi target is -120 to -100 V, and the current is 80 to 160 A.
[0013] Preferably, in step S1, the bias voltage of the Cr target is -100 V, the current is 60 A, and the deposition time is 10 min.
[0014] Preferably, in step S2, the current of the TiSi target is 80A, 100A, 120A, 140A or 160A.
[0015] More preferably, in step S2, the deposition time is 30 min; the bias voltage of the CrAl target is -80 V, and the target current is 120 A; the bias voltage of the TiSi target is -100 V, and the target current is 140 A; 2 The flow rate is 200sccm.
[0016] Preferably, the method further comprises the step of cleaning the substrate before step S1.
[0017] More preferably, the method further comprises heating the coating chamber to remove pollutants before step S1.
[0018] Preferably, the method further comprises the step of introducing Ar to etch the surface of the substrate before step S1.
[0019] More preferably, the coating chamber is heated to 400-500° C. before step S1;
[0020] The Ar was introduced under a bias voltage of -400 V to etch the substrate surface for 20 minutes.
[0021] To achieve the above objectives, the present disclosure also provides the following technical solutions:
[0022] A CrAlTiSiN coating, wherein the CrAlTiSiN coating is obtained by any of the preparation methods described above; in the CrAlTiSiN coating, the Ti content is 9 to 21 at.%, and the Si content is 4 to 12 at.%.
[0023] Preferably, the Ti content is 16.41 at.%, and the Si content is 5.70 at.%.
[0024] The technical solution claimed in the present disclosure has achieved the following beneficial effects:
[0025] When Ti=16.41at.% and Si=5.70at.% in the prepared CrAlTiSiN coating, the CrAlTiSiN coating has the best crystallinity and the most compact structure. The hardness, elastic modulus and fracture toughness of the CrAlTiSiN coating are all improved, and the measured values are 35.9GPa, 294.1GPa and 1.53MPa·m 1 / 2 , the internal stress of the coating is -0.34 GPa, the corrosion potential of the coating moves in the positive direction, and the corrosion current density is 1.60×10 -8 A.cm -2 , indicating that CrAlTiSiN coating has the best corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present disclosure, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings in the following description are merely embodiments of the present disclosure, and a person of ordinary skill in the art can obtain other drawings based on the provided drawings without paying any creative work.
[0027] Figure 1 SEM surface scanning element distribution diagram of CrAlTiSiN coating with different TiSi contents: (a) #1: Ti = 10.42 at.%, Si = 11.66 at.%, (b) #2: Ti = 11.97 at.%, Si = 8.00 at.%, (c) #3: Ti = 14.06 at.%, Si = 6.16 at.%, (d) #4: Ti = 16.41 at.%, Si = 5.70 at.%, (e) #5: Ti = 20.60 at.%, Si = 4.35 at.%.
[0028] Figure 2Effect of different TiSi contents on the surface morphology of CrAlTiSiN coatings: (a) #1: Ti = 10.42 at.%, Si = 11.66 at.%, (b) #2: Ti = 11.97 at.%, Si = 8.00 at.%, (c) #3: Ti = 14.06 at.%, Si = 6.16 at.%, (d) #4: Ti = 16.41 at.%, Si = 5.70 at.%, (e) #5: Ti = 20.60 at.%, Si = 4.35 at.%.
[0029] Figure 3 XRD patterns of CrAlTiSiN coatings with different TiSi contents.
[0030] Figure 4 HRTEM cross-sectional morphology of CrAlTiSiN coating when Ti=16.41at.% and Si=5.70at.%: (a) low magnification, (b) high magnification and selected area electron diffraction pattern.
[0031] Figure 5 Hardness and elastic modulus of CrAlTiSiN coatings with different TiSi contents.
[0032] Figure 6 This is the internal stress variation curve of CrAlTiSiN coating with different TiSi contents.
[0033] Figure 7 Berkovich indentation morphologies of CrAlTiSiN coatings with different TiSi contents at a depth of 2400 nm: (a) #1: Ti = 10.42 at.%, Si = 11.66 at.%, (b) #2: Ti = 11.97 at.%, Si = 8.00 at.%, (c) #3: Ti = 14.06 at.%, Si = 6.16 at.%, (d) #4: Ti = 16.41 at.%, Si = 5.70 at.%, (e) #5: Ti = 20.60 at.%, Si = 4.35 at.%.
[0034] Figure 8 This is the curve of fracture toughness of CrAlTiSiN coating changing with total TiSi content.
[0035] Fig. 9 Polarization curves of CrAlTiSiN coatings with different TiSi contents in 3.5wt.% NaCl solution. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and beneficial effects of the embodiments of the present disclosure clearer, the technical solution in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.
[0037] Example
[0038] The coating equipment used in this embodiment is a multi-arc ion coating equipment, and the targets used are Cr target, TiSi target and Cr 50 Al 50 Alloy target, the purity of the target material is 99.99%, TiSi target and Cr 50 Al 50 The alloy targets are installed on opposite sides of the vacuum chamber. The working gas is high-purity argon (Ar) and nitrogen (N 2 ), in the vacuum chamber, the distance between each target and the substrate is the same, which is 240 mm.
[0039] In the coating experiment, the substrates were mounted on rotating brackets, which rotated at 6 rpm. The substrate materials used in this embodiment are polished 316 stainless steel sheets and pure Si sheets, where the stainless steel sheets with a size of 20 mm × 20 mm × 1 mm are used for mechanical properties and corrosion resistance, and the film thickness test of the coating uses a pure Si sheet with a size of 20 mm × 5 mm × 1 mm.
[0040] The preparation process of the CrAlTiSiN coating in this embodiment is as follows:
[0041] 1) Experimental sample cleaning steps: Put the polished stainless steel sheet and Si sheet into beakers containing propanol and anhydrous ethanol respectively and ultrasonically clean them for at least 30 minutes. After drying, install them in a vacuum chamber;
[0042] 2) The chamber was vacuumed to 2.0×10 -3 Pa, before coating, the temperature of the vacuum chamber is heated to 450 ° C, the purpose of which is to eliminate tiny liquid and solid contaminants in the vacuum chamber and on the surface of the substrate;
[0043] 3) Pass high-purity Ar, turn on the bias power supply to -400V, pass Ar to etch the substrate surface for 20 minutes to remove impurities on the substrate, then lower the bias voltage to -100V and continue to pass Ar for 2 minutes;
[0044] 4) Turn off Ar and introduce N 2, turn on the Cr target, and prepare the CrN transition layer under the conditions of deposition bias voltage of -100V and target current of 60A, wherein the deposition time is 10min. The purpose of preparing the CrN transition layer is to facilitate improving the bonding strength between film layers;
[0045] 5) Continue to pass N 2 , turn off the Cr target and start the Cr 50 Al 50 target and TiSi target, in N 2 CrAl and TiSi were deposited on the substrate at a flow rate of 100 to 300 sccm to obtain a CrAlTiSiN coating. The deposition time was 30 min. Finally, the sample was cooled to room temperature in the furnace and then taken out.
[0046] Among them, Cr 50 Al 50 The bias voltage of the target is -100 to -90 V, and the current is 110 to 130 A; the bias voltage of the TiSi target is -120 to -100 V, and the current of the TiSi target is 80 to 160 A.
[0047] In a preferred embodiment, the current of the TiSi target is set to 80A, 100A, 120A, 140A and 160A respectively.
[0048] In a more preferred embodiment, Cr 50 Al 50 The target bias voltage is -80V, the target current is 120A; the TiSi target bias voltage is -100V, N 2 The flow rate is 200sccm.
[0049] In this embodiment, when Cr 50 Al 50 The target bias voltage is -80V, the target current is 120A, the TiSi target bias voltage is -100V, N 2 Under the condition of a flow rate of 200 sccm, when the current of the TiSi target is set to 80A, 100A, 120A, 140A and 160A respectively, CrAlTiSiN coatings with TiSi contents of (#1) Ti = 10.42at.%, Si = 11.66at.%, (#2) Ti = 11.97at.%, Si = 8.00at.%, (#3) Ti = 14.06at.%, Si = 6.16at.%, (#4) Ti = 16.41at.%, Si = 5.70at.%, (#5) Ti = 20.60at.%, Si = 4.35at.% can be obtained.
[0050] In this embodiment, the performance of each CrAlTiSiN coating sample obtained is characterized by scanning electron microscopy (SEM) and energy dispersive spectrometer (EDS), X-ray diffractometer (XRD), high resolution transmission electron microscopy (HRTEM), atomic force microscopy (AFM), coating stress tester, nanoindenter and electrochemical corrosion test.
[0051] Figure 1 The SEM surface scanning element distribution of CrAlTiSiN coatings with different TiSi contents is shown. The distribution of each element in the CrAlTiSiN coatings with different TiSi contents is relatively uniform. Figure 2 The effect of TiSi content on the surface morphology of CrAlTiSiN coating is shown. When Ti = 16.41 at.%, Si = 5.70 at.%, the surface roughness of CrAlTiSiN coating is the smallest and the structure is the densest, indicating that reasonable control of TiSi content improves the surface density and surface porosity of CrAlN-based coating.
[0052] Figure 3 The XRD patterns of the CrAlTiSiN coatings with different TiSi contents are shown. The results indicate that the CrAlTiSiN coating obtained in this example has an FCC structure, and the preferred orientations are CrN (111) and (200). Figure 4 The HRTEM cross-sectional morphology of the CrAlTiSiN coating when Ti=16.41at.% and Si=5.70at.% is shown, indicating that the CrAlTiSiN coating under this condition has good crystallization properties.
[0053] Figures 5 to 8 The hardness and elastic modulus, internal stress, Berkovich indentation morphology and fracture toughness of the CrAlTiSiN coating with different TiSi contents are shown respectively. From the above results, it can be seen that when Ti = 16.41at.% and Si = 5.70at.%, the hardness, elastic modulus and fracture toughness of the CrAlTiSiN coating are improved, which are 35.9GPa, 294.1GPa and 1.53MPa·m respectively. 1 / 2 , the internal stress of the coating is -0.34GPa.
[0054] Fig. 9 The polarization curves of CrAlTiSiN coatings with different TiSi contents in 3.5wt.% NaCl solution are shown. When Ti=16.41at.%, Si=5.70at.%, the corrosion potential of CrAlTiSiN coating moves to the positive direction, and the maximum corrosion current density is the smallest, which is 1.60×10 -8 A.cm -2 , indicating that the CrAlTiSiN coating has the best corrosion resistance under this process parameter.
[0055] The coating obtained in this embodiment can be used for surface protection of cutting tools and mechanical friction parts to improve the surface performance and service life of the tools and parts. The preparation method also has the advantages of simple process, fast deposition speed, low cost and high bonding strength.
[0056] Comparative Example
[0057] This comparative example provides the preparation of CrAlN coating.
[0058] The coating equipment used in this comparative example is a multi-arc ion plating equipment, and the targets used are Cr target and Cr 50 Al 50 Alloy target, the purity of the target material is 99.99%, and the two targets are installed on opposite sides of the vacuum chamber. The working gas is high-purity argon (Ar) and nitrogen (N 2 ), in the vacuum chamber, the distance between each target and the substrate is the same, which is 250 mm. In the coating experiment, the substrates are respectively mounted on rotating brackets and rotated at a speed of 6 rpm. The substrate materials selected in this embodiment are polished 316 stainless steel sheets and pure Si sheets, of which the stainless steel sheets with a size of 20 mm × 20 mm × 1 mm are used for the characterization of mechanical properties and corrosion resistance, and the film thickness test of the coating uses a pure Si sheet with a size of 20 mm × 5 mm × 1 mm.
[0059] The preparation process of the CrAlN coating in this embodiment is as follows:
[0060] 1) Experimental sample cleaning steps: Put the polished stainless steel sheet and Si sheet into beakers containing propanol and anhydrous ethanol respectively and ultrasonically clean them for at least 30 minutes. After drying, install them in a vacuum chamber;
[0061] 2) The chamber was vacuumed to 2.0×10 -3 Pa, before coating, the temperature of the vacuum chamber is heated to 450 ° C, the purpose of which is to eliminate tiny liquid and solid contaminants in the vacuum chamber and on the surface of the substrate;
[0062] 3) Pass high-purity Ar, turn on the bias power supply to -400V, pass Ar to etch the substrate surface for 20 minutes to remove impurities on the substrate, then lower the bias voltage to -100V and continue to pass Ar for 2 minutes;
[0063] 4) Turn off Ar and introduce N 2 , turn on the Cr target, and prepare the CrN transition layer under the conditions of deposition bias voltage of -100V and target current of 60A, wherein the deposition time is 10min. The purpose of preparing the CrN transition layer is to facilitate improving the bonding strength between film layers;
[0064] 5) Continue to pass N2 , turn off the Cr target and start Cr 50 Al 50 Target, bias voltage is -80V, arc current is 120A, N 2 CrAl was deposited on the substrate at a flow rate of 200 sccm to obtain a CrAlN coating. The deposition time was 40 min. Finally, the sample was cooled to room temperature in the furnace and then taken out.
[0065] The maximum values of hardness, elastic modulus and fracture toughness of CrAlN coating are 30.7 GPa, 290.7 GPa and 1.41 MPa·m respectively. 1 / 2 , the minimum internal stress is 0.32GPa, and the corrosion current density is 6.65×10 -8 A.cm -2 Compared with the CrAlN coating, the hardness of the CrAlTiSiN coating with Ti=16.41at.% and Si=5.70at.% increased by 5.9GPa, the elastic modulus and fracture toughness values increased, and the corrosion current density decreased significantly. This shows that the doping of TiSi effectively improves the performance of the CrAlN coating.
[0066] The embodiments described above are merely illustrative descriptions of the present disclosure and are not intended to limit the scope of the present disclosure. Without departing from the design spirit of the present disclosure, various modifications and improvements made to the technical solutions of the present disclosure by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present disclosure.
Claims
1. A method for preparing a CrAlTiSiN coating, characterized in that: The following steps are involved: S1. N2 is introduced into the coating chamber, the Cr target is started, and a CrN transition layer is deposited on the substrate; S2. Continue to introduce N2, turn off the Cr target, and start Cr 50 Al 50 target and a TiSi target, depositing CrAl and TiSi on the substrate under a N2 flow rate of 100 to 300 sccm to obtain a CrAlTiSiN coating; Among them, the Cr 50 Al 50 The bias voltage of the target is -100 to -90 V, and the current is 110 to 130 A; the bias voltage of the TiSi target is -120 to -100 V, and the current is 80 to 160 A.
2. The preparation method according to claim 1, characterized in that: In step S1, the bias voltage of the Cr target is -100 V, the current is 60 A, and the deposition time is 10 min.
3. The preparation method according to claim 1, characterized in that: In step S2, the current of the TiSi target is 80A, 100A, 120A, 140A or 160A.
4. The preparation method according to claim 3, characterized in that: In step S2, the deposition time is 30 min; the Cr 50 Al 50 The bias voltage of the target is -80 V, and the target current is 120 A; the bias voltage of the TiSi target is -100 V, and the target current is 140 A; the flow rate of N2 is 200 sccm.
5. The preparation method according to claim 1, characterized in that: The method also includes the step of cleaning the substrate before step S1.
6. The preparation method according to claim 1, characterized in that: The process also includes heating the coating chamber to remove contaminants before step S1.
7. The preparation method according to claim 6, characterized in that: The method further comprises the step of introducing Ar to etch the surface of the substrate before step S1.
8. The preparation method according to claim 7, characterized in that: Before step S1, the coating chamber is heated to 400-500°C; The Ar was introduced under a bias voltage of -400 V to etch the surface of the substrate for 20 minutes.
9. A CrAlTiSiN coating, characterized in that: The CrAlTiSiN coating is obtained by the preparation method according to any one of claims 1 to 8; in the CrAlTiSiN coating, the Ti content is 9 to 21 at.%, and the Si content is 4 to 12 at.%.
10. The CrAlTiSiN coating according to claim 9, characterized in that: The Ti content is 16.41 at.%, and the Si content is 5.70 at.%.
Citation Information
Patent Citations
CrAlTiSiN cutter protective coating and preparation method thereof
CN105839054A
Special coated tool for processing stainless steel, and preparation method thereof
CN108103465A
Cr / CrN / CrAlSiN / CrAlTiSiN nano-multilayer gradient film and preparation method thereof
CN109295425A
CrAlTiSiCN nano-composite coating and preparation method thereof
CN112962059A
Stainless steel composite material and preparation method thereof
CN116555716A